Physical activity and its relationship with health-related quality of life in type II diabetics - Eliana Romina Meza-Miranda; Beatriz Elizabeth Núñez-Martínez (University of Novi Sad, Faculty of Sport and Physical Education, 2022)
Due to the chronic nature of the disease, type II Diabetes mellitus (DM2) can affect the quality of life and perception of health. The objective of this study was to evaluate the quality of life, perception of health, and level of physical activity in type II diabetics in December 2021. A descriptive, analytical cross-sectional design study, which included 116 volunteers with DM2 through an online survey where sociodemographic data, quality of life according to the EuroQoL-5D, health perception according to a visual analog scale, and level of physical activity according to the international IPAQ questionnaire. The study was approved by the Scientific and Ethics Committee of the Paraguayan Association of Graduates in Nutrition (code number 128/2021). The average age was 51.9 years, 63.8 were female, 79.3% resided in Asunción and the Metropolitan Area, and 39.5% had a secondary education level. 94% continued treatment, hypertension being the most frequent comorbidity. The quality of life showed 38% with moderate depression and/or anxiety. The quality-of-life index was 0,62±0.12 and the perception of health was 65.3±17.6. The predominant level of physical activity was low (45%). When comparing the quality-of-life index and the perception of health according to the level of physical activity, it was found that these variables showed better scores in those who perform moderate to high physical activity. The level of physical activity is a determinant of health-related quality of life, the greater the intensity of physical activity, the better the quality and perception of health indices in diabetics patients.